2008
DOI: 10.1002/ejic.200700943
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Brookite‐Type TiO2/Carbon Nanocomposite Electrodes for Application to Li Ion Batteries

Abstract: The increasing demand for portable energy has generated significant research interest in nanostructured electrode materials, because of their large interfacial contact area with the electrolyte and short path lengths for Li ion transport. To date, titanium dioxide (TiO 2 ) has been widely investigated as an electroactive, Li-insertion host. However, the lithium reactivity of brookite-type TiO 2 has rarely been addressed compared to the common polymorphs, anatase and rutile, because of the difficulties encounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 31 publications
2
29
0
1
Order By: Relevance
“…Further studies revealed that the reversibility of Li insertion decreased with an increase in crystallite size of brookite [126]. Hybrid multi-walled carbon nanotube/brookite electrodes improved the specific capacity and capacity retention on cycling [127,128]. Dambournet et al [63] prepared micrometer-size mesoporous brookite electrodes with a high specific area that provided higher volumetric energy density in a lithium ion battery than anatase or rutile electrodes.…”
Section: Pure Brookitementioning
confidence: 99%
“…Further studies revealed that the reversibility of Li insertion decreased with an increase in crystallite size of brookite [126]. Hybrid multi-walled carbon nanotube/brookite electrodes improved the specific capacity and capacity retention on cycling [127,128]. Dambournet et al [63] prepared micrometer-size mesoporous brookite electrodes with a high specific area that provided higher volumetric energy density in a lithium ion battery than anatase or rutile electrodes.…”
Section: Pure Brookitementioning
confidence: 99%
“…[37]. Another pair of broad peaks (at 1.45 and 1.75 V) associated with differing site occupations might be attributed to the formation of the discrete phase or imperfection of the TiO 2 lattice, which facilitate the transport of Li through surface defects and in bulk materials [16]. The content of TiO 2 is low and carbon shell is the dominant phase in sample #1.…”
Section: Resultsmentioning
confidence: 99%
“…To address the negative issues, TiO 2 in various nanocrystalline forms are widely used to reduce the diffusion path length for lithium-ions and increase high contact area between electrolyte and electrode, thereby improving both storage capacity and rate capability [11][12][13]. Another common strategy involves incorporation of TiO 2 with carbonaceous materials, which can enhance the electronic conductivity and suppress the aggregation of TiO 2 nanocrystals, thus increasing the anode stability during cycling [14][15][16]. Consequently, TiO 2 @carbon nanocomposite is considered as a promising high-performance anode material in LIBs, and several synthesis methods have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was based on that of Pottier, et al [84] which yielded similar particle size and morphology. In a separate study, Lee, et al [85] dissolved urea in an aqueous solution containing titanium trichloride (TiCl 3 ), and refluxed the solution at 100°C for 7 hours. This process produced large aggregates of nanospherical, 10-20 nm crystallites.…”
Section: Brookitementioning
confidence: 99%
“…They made electrodes by mixing brookite active material with acetylene black and PVDF in a weight ratio of 70:20:10, and were able to achieve a reversible capacity of 170 mA h g −1 over 40 cycles at a 35 mA g −1 (corresponding to a rate of C/10; 1 Li in 10 hours). Lee, et al [85] compared pristine brookite (mixed with super P and PVDF in a ration of 68:20:12) and composites of brookite with multi walled carbon nanotubes (MWCNT) using the same binder ratio, but replacing super P with composite active material. At C/5 rate (in this case corresponding to 0.5 Li in 5 hours), reversible capacity of 160 mA h g −1 was achieved over 50 cycles.…”
Section: Brookitementioning
confidence: 99%